Who benefits from job training programmes? Evidence from a high-dosage programme in Brazil - Daniel Da Mata; Rodrigo Carvalho Oliveira; Diana Lúcia Gonzaga Da Silva (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Using admission lotteries and registry data linking labour market outcomes, we study the effect of a vocational training programme focused on disadvantaged individuals in Brazil. The intensive programme is an 18-month classroom training coupled with a 6-month on-the-job training provided by government-sponsored training centres. When assessing the impacts on 15,000 winners and 200,000 non-winners who graduated in different business cycle moments, we show that female students fare better than their male counterparts. Results are driven by courses in services and those located in faster-growing local labour markets. Investigating outcomes beyond employment and earnings, we do not find an impact on entrepreneurship or university admission.
Keywords: I26; I28; J24; L26; 330; job training programmes; employment; entrepreneurship